Pre-service teachers’ views of their training: key issues to sustain quality teacher education - Flores, Maria Assunção (2014)
This paper draws upon data from a broader piece of research aimed at examining preservice teachersí views of their initial teacher education within the context of a masterís degree programme in teaching. The data were collected through questionnaires and written narratives at the beginning and at the end of the programme. In this paper, the data arising from 47 narratives at the end of the programme are presented. Five categories emerged from the qualitative data: curriculum content, teaching practice, the role of teacher educators, teaching and learning methods, the organisational aspects and structure of the programme. Although the participants identified positive aspects of the initial teacher education programme, they also stress that there is room for improvement, especially with regard to a greater coherence of the curriculum and a better articulation of its different components. Implications of the findings for enhancing the quality of initial teacher education and the role of teachersí educators are discussed.